Growth and fuelwood production of Cassia siamea and Eucalyptus camaldulensis under short rotation in the eastern Terai of Nepal - Thapa, H.B.; Subedi, N. (Banko Janakari, 2017)
Abstract available on the PDF Banko Janakari Vol.11(2) 2001: 34-41